(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The study objective to determine the extent to which the principles of continuous improvement are applied in the field of innovation in banking services and industry, by relying on technological development in the banking industry and administrative systems in order to achieve customer satisfaction and increase confidence in banking services, by providing banking services that keep pace with the automation of banking operations and in line with the trends The Central Bank is in the transition to electronic money, so the research stems from an important intellectual provocation, namely, do Iraqi banks use continuous improvement techniques and what are the criteria for evaluating their services? The research also aims to track the development of the characteristics of services according to the development of the financial needs of customers and to know the nature of the relationship between the principles of CI and the characteristics of BS. , standard deviation, correlation coefficient, coefficient of determination) that the most important characteristics of BS are understandable to the customer, and this depends on the employees and the declared policy of the bank.